PROBLEMATIKA ETIKA DALAM PRAKTIK ADVOKASI PADA KASUS-KASUS DI INDONESIA - Brahmana, Febi Febonecci S.; Putri, Helmalia; Yusuf, Dhea Ananda Puspita; Siregar, Halimatusaddiah; Nasution, Habibi Irham Buana; Nasution, Nazri Adhlani (Cahaya Ilmu Bangsa, 2024)
Ethical problems in advocacy practice are complex and crucial issues for the sustainability and public trust in the legal profession. This study aims to identify factors that contribute to ethical violations in advocate practice, as well as review the effectiveness of the applicable code of ethics. Using the desk research method, this study collected data from various relevant literature, including scientific journals, reference books, code of ethics regulations, and reports from advocate professional organizations. The results show that ethical dilemmas in the advocate profession often arise due to conflicts of interest, pressure from clients, and a lack of understanding of ethical values. External factors, such as economic demands and socio-political influences, also play an important role in encouraging violations of the code of ethics. Although the code of ethics for advocates has been implemented, its effectiveness still needs to be improved through stronger supervisory mechanisms, continuous ethics training, and strict sanctions for violators. By strengthening these aspects, it is hoped that advocates will be able to carry out their functions with greater integrity, thereby increasing public trust in the justice system. Problematika etika dalam praktik advokasi merupakan isu yang kompleks dan krusial bagi keberlangsungan serta kepercayaan publik terhadap profesi hukum. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang berkontribusi terhadap pelanggaran etika dalam praktik advokat, serta meninjau efektivitas kode etik yang berlaku. Menggunakan metode penelitian pustaka, kajian ini mengumpulkan data dari berbagai literatur terkait, termasuk jurnal ilmiah, buku referensi, regulasi kode etik, dan laporan dari organisasi profesi advokat. Hasil penelitian menunjukkan bahwa dilema etika dalam profesi advokat sering kali muncul akibat konflik kepentingan, tekanan dari klien, dan kurangnya pemahaman tentang nilai-nilai etis. Faktor eksternal, seperti tuntutan ekonomi dan pengaruh sosial-politik, juga memainkan peran penting dalam mendorong pelanggaran kode etik. Meskipun kode etik profesi advokat sudah diterapkan, efektivitasnya masih perlu ditingkatkan melalui mekanisme pengawasan yang lebih kuat, pelatihan etika berkelanjutan, serta sanksi tegas bagi pelanggar. Dengan penguatan pada aspek-aspek ini, diharapkan advokat dapat menjalankan fungsinya dengan integritas yang lebih tinggi, sehingga kepercayaan publik terhadap sistem peradilan juga meningkat.